Pengaruh Terapi Musik Instrumentalia Terhadap Penurunan Intensitas Nyeri Persalinan Kala I Aktif Di 3 Bidan Praktek Mandiri Ngemplak Boyolali - KH Endah Widhi Astuti; RD Rahayu; Noris Hadi Sri Mulyani (Jurnal Kebidanan dan Kesehatan Tradisional, 2016)
Absctract: Music Therapy, Pain Intensity, Active Phase Of The First Stage Of Labor. Pain during labor is a physiological condition. In the physiology of labor, pain began to arise in the latent phase of the first stage of labor and the active phase. The intensity of pain during labor affects the psychological condition of the mother, labor, and fetal well-being. To know the effect of instrumental music therapy on decreasing the intensity of pain labor during the active phase on the first stage of labor in 3 indepndent midwives practice in ngemplak Boyolali district. Type of pre-experimental research with one group pretest-posttest design. Population of this study is mother actice phase in the first stage of labor in three independents midwives in Ngemplak Boyolali between October 2013 to December 2013. The sampling used purposive sampling technique with a sample of 32 respondents. The measurement technique used a pain scale. The Data was processed by editing, coding, scoring and tabulating. The Data was analysed used a paired sample t-test. The majority of respondents aged between 20-35 years (93.8%)with 2 children (43.8%), the level of high school education (56.3%), the overall family support (100%) and less anxious (65.6%). Numerical pain l evels before therapy is the majority of severe pain (68.8%) and after music therapy decreased the numerical pain becomes moderate pain (78.1%). The level of pain behavior before the majority of instrumental music therapy is severe pain and being with each 16 persons (50.0%) and after intrumentalia music therapy decreased pain is pain with the majority being about 18 people (56.3%). There is effect instrumental music therapy to decrease pain intensity numeric and the intensity of pain behavior in the labor Kala I active (0.000 < 0.05). There is the effect of instrumental music therapy on decreasing the intensity of pain inthe actve phase of the first stage of labor.